Sundanese Cultural Integration in English Learning: Insights from Young Learners and Parents - Alwasilah, Indiana Ayu (Mimbar Sekolah Dasar, 2024)
Amidst globalization, there is an emerging issue to strengthen students’ local identity since the trend of English teaching is shifting from using English-speaking culture materials into integrating local culture. As a multicultural country, Indonesia has great potential to incorporate local culture into education. This concept, known as ethnopedagogy, utilizes local culture to strengthen genuine Indonesian education, considering that local culture is a source of innovation and skills that can be empowered in the classroom. Therefore, this research investigates the insights of young learners (aged 10-11 years old) regarding Sundanese cultural integration in their English language learning. Guided by an interpretivist paradigm, this qualitative case study seeks to explore the students’ learning experiences and insights. This research involved a class of English for Young Learners class in one of English language courses in Bandung, West Java, Indonesia. Data were collected using classroom observation, interview, and field notes. The findings revealed that integrating Sundanese culture into English lessons was a novel experience for the students, differing significantly from their school-based English learning. Furthermore, this approach fostered a sense of participation in preserving culture since students had better understanding about their own culture. In addition, it contributed to improvement in attention span, excitement, memory, knowledge, English score at school, and students relationship. Also, parents appreciated Sundanese culture integration into their children’s English learning. They perceived it as a means to preserve Sundanese culture while also support their cultural values and educational foundation at home and help them navigate the challenges of modern society.